Sign language : an international handbook - Pfau, Roland, 1966-; Steinbach, Markus, 1967-; Woll, B. (Bencie), 1950- (Berlin : De Gruyter Mouton, 2012)
Sign language linguists show here that all questions relevant to the linguistic investigation of spoken languages can be asked about sign languages. Conversely, questions that sign language linguists consider - even if spoken language researchers have not asked them yet - should also be asked of spoken languages. The HSK handbook Sign Language aims to provide a concise and comprehensive overview of the state of the art in sign language linguistics. It includes 44 chapters, written by leading researchers in the field, that address issues in language typology, sign language grammar, psycholinguistics, neurolinguistics, sociolinguistics, and language documentation and transcription. Crucially, all topics are presented in a way that makes them accessible to linguists who are not familiar with sign language linguistics.
I. Phonetics, phonology, and prosody -- II. Morphology -- III. Syntax -- IV. Semantics and pragmatics -- V. Communication in the visual modality -- VI. Psycholinguistics and neurolinguistics -- VII. Variation and change -- VIII. Applied issues -- IX. Handling sign language data -- Indexes
Elektronická reprodukce.
Keywords: znakový jazyk; sign language; příručky; e-knihy online; handbooks and manuals; e-books online